2015
DOI: 10.1038/cr.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group protein-mediated transcription requires DNA damage marker γ-H2AX

Abstract: The eukaryotic genome is organized into chromatins, the physiological template for DNA-dependent processes including replication, recombination, repair, and transcription. Chromatin-mediated transcription regulation involves DNA methylation, chromatin remodeling, and histone modifications. However, chromatin also contains non-histone chromatin-associated proteins, of which the high-mobility group (HMG) proteins are the most abundant. Although it is known that HMG proteins induce structural changes of chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 58 publications
8
84
1
Order By: Relevance
“…HMGA2 Ser 44 is within the CDK2 kinase substrate motif[60] and Ser 102 is within the ATM kinase substrate motif. Recent studies indicate that HMGA2 can be phosphorylated by ATM, and TGFβ1-induced transcription requires the interplay between HMGA2, ATM and H2AX phosphorylation [61, 62], implying that ATM kinase may play a role in regulating EMT through HMGA2. We also observed the upregulation of phosphorylation of Ser 73 of transcription factor AP1/c-JUN in EMT-hSAECs.…”
Section: Discussionmentioning
confidence: 99%
“…HMGA2 Ser 44 is within the CDK2 kinase substrate motif[60] and Ser 102 is within the ATM kinase substrate motif. Recent studies indicate that HMGA2 can be phosphorylated by ATM, and TGFβ1-induced transcription requires the interplay between HMGA2, ATM and H2AX phosphorylation [61, 62], implying that ATM kinase may play a role in regulating EMT through HMGA2. We also observed the upregulation of phosphorylation of Ser 73 of transcription factor AP1/c-JUN in EMT-hSAECs.…”
Section: Discussionmentioning
confidence: 99%
“…γH2AX induces changes of chromatin that inhibit the assembly of transcription complexes without heterochromatin formation [28]. In addition, recent studies showed that γH2AX is required for high mobility group protein-mediated transcription [29]. Here, we showed that γH2AX could bind to the promoter of miR-3196 and regulate the expression of the apoptotic protein PUMA through miR-3196.…”
Section: Discussionmentioning
confidence: 83%
“…In a recently published study in Cell Research, Singh and collaborators [6] provide further evidence supporting a connection between transcription and DNA repair in the context of the TGFβ1 signaling during epithelial-mesenchymal transition (EMT). The authors use a combination of proteomics-based interactome analysis, ChiP-seq and expression microarrays to propose a novel mechanism of transcriptional activation, which requires HMGA2 and the well-established DNA damage marker H2AX phosphorylated by ATM at S139 (γ-H2AX) (Figure 1).…”
Section: Npgmentioning
confidence: 99%